Mitral valve replacement at Tygerberg Hospital: a 5 year follow-up - Barnard, B.J.; le Roux, P.J. (SA Heart Journal, 2017)
This study provides 5-year follow-up data of isolated mitral valve replacements with mechanical prosthesis at a large South African tertiary hospital. It also assessed the significance of pre-operative parameters to predict mortality. This is a retrospective study of 187 patients that underwent isolated mitral valve replacement at Tygerberg Hospital from Jan 1998-Dec 2002. Twenty seven patient’s data was incomplete and they were excluded from the study. All patients had rheumatic mitral valve disease and the valve lesions included mitral incompetence, mitral stenosis and mixed mitral valve disease. All patients had a mechanical prosthesis implanted (St Jude medical or Orbis bileaflet valves). The mean follow-up time was 5.41-years. The 30 day mortality was 5.62% and the 5-year survival was 80%. Pre-operative risk factors that significantly increased mortality were pulmonary hypertension and mitral stenosis. Valve-related complications were more common in this series compared to other First World populations but our results compare well with other Third World population groups. Valve thrombosis 4.32% (0.8%/yr), thromboembolism 8.71% (1.61%/yr), anticoagulant related haemorrhage 6.87% (1.27%/yr), prosthetic valve endocarditis 3.08% (0.57%/yr) and re-operation 8.12% (1.5%/yr). Conclusion: Mechanical valve replacement for mitral valve disease that requires valve replacement is still a good treatment option even in third world population groups. In our series, severe pulmonary hypertension, mitral stenosis and reoperation was statistically significantly more common in the “non-survivors” group.